Ação do tratamento com Mentha piperita L. e Harpagophytum procumbens contra Schistosoma mansoni - in vitro: análise proteômica - Correia, Ricardo de Oliveira (2014)
Mansonic schistosomiasis is a disease that infected more than 240 million people worldwide, it is caused by Schistosoma mansoni. It is the second only to malaria in public health importance. The only drug currently effective against S. mansoni is Praziquantel (PQZ), however, has been reported strains of S. mansoni with loss of sensitivity. Such reports reinforce the need to develop new safer treatment against S. mansoni. The natural compounds are important to develop new drugs. Mentha piperita L. also known as peppermint, studies reported the treatment as antiparasitic diseases (for example giardiasis). In ours laboratory showed a decrease of inflammatory process of schistosomiasis in a murine model after treatment with ethanolic extract of M. piperita. However don´t know nothing about action of this plant against adult worms of S. mansoni. Harpagophytum procumbens is a plant that has origins in Africa, studies showed promising results antibacterial and against rheumatism diseases, but has no studies against schistosomiasis. In this study we evaluated effect of ethanolic extract of H. procumbens and ethanolic extract of Mentha piperita L. and its fractions against Schistosoma mansoni, its observed for optical microscopic and change in protein expression, after in vitro assay. It was observed that all extract and its fraction caused the motor activity reduction and separation of couple worms. Exceptions of hydroalcoholic fraction of M. piperita, S. mansoni adult worms were death after treatment. We observed that ethanolic extract of H. procumbens showed more promising results when compared with M. piperita. And we observed that ethyl acetate shoed more promising result than ethanolic extract of M. piperita and its other fractions.In this work was observed change in protein expression in 2D gel electrophoresis after all ethanolic extractions and fractions treatment. The proteins in gel electrophoresis have been identified by mass spectrometry. The mass spectrometry assay showed important proteins for S. mansoni homeostasis and possible therapeutic target, for example actin, enolasis, fructose-biphosphate aldolase, and others important proteins. These results indicate that these plants may be anthelmintic activity against S. mansoni. However, it has need for more studies to complete undesiring of these extract against S. mansoni.